2021
DOI: 10.5312/wjo.v12.i9.700
|View full text |Cite
|
Sign up to set email alerts
|

Trends and risk factors for opioid administration for non-emergent lower back pain

Abstract: BACKGROUND Non-emergent low-back pain (LBP) is one of the most prevalent presenting complaints to the emergency department (ED) and has been shown to contribute to overcrowding in the ED as well as diverting attention away from more serious complaints. There has been an increasing focus in current literature regarding ED admission and opioid prescriptions for general complaints of pain, however, there is limited data concerning the trends over the last decade in ED admissions for non-emergent LBP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The lack of quantitative characterization of the association between opioid or sedative use and outcomes after nonemergency spine surgery among published investigations hinders a data-driven patient-specific risk assessment in clinical settings 4,8–11,30. The present study found that higher preoperative NCS-opioids, especially those above 300, are associated with an approximately twofold increase in the risk of prolonged LOS and 90-day readmission in addition to a potentially significant association with a higher incidence of 90-day reoperation as outlined by the propensity score-matched comparison.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…The lack of quantitative characterization of the association between opioid or sedative use and outcomes after nonemergency spine surgery among published investigations hinders a data-driven patient-specific risk assessment in clinical settings 4,8–11,30. The present study found that higher preoperative NCS-opioids, especially those above 300, are associated with an approximately twofold increase in the risk of prolonged LOS and 90-day readmission in addition to a potentially significant association with a higher incidence of 90-day reoperation as outlined by the propensity score-matched comparison.…”
Section: Discussionmentioning
confidence: 52%
“…1 In spine disorders, opioids and sedatives remain among the most commonly prescribed, dispensed, and consumed medications for acute as well as chronic back relief. [2][3][4][5] Such pattern persists despite several resolute medical as well as legislative reforms and the increasing body of contemporary literature that disputes the pain relief efficacy of opioids and sedatives compared to nonsteroidal anti-inflammatory medications or even placebo. [6][7][8][9] The association between preoperative opioid or sedative use and adverse postoperative outcomes remains controversial.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The main limitation of this study is the potential for unmeasured confounders to influence results. Certain variables that may influence the likelihood of tramadol prescription are unavailable or poorly represented in the TriNetX dataset, including pain severity,58 60 income,60 insurance type,60 geographic location,60 type of medical clinician seen,74 75 education level,59 marital status,59 patients’ requests for medication (ie, pressure to prescribe), or conversely, reluctance to consider taking a prescription opioid 36 37 76. Although the TriNetX database contains medical record data, we did not have access to detailed patient charts to directly validate our results due to the deidentified, aggregated nature of the dataset sourced from multiple healthcare organisations.…”
Section: Discussionmentioning
confidence: 99%
“…Social determinants of health: problems related to education59 and economic circumstances (positive)60…”
Section: Variablesmentioning
confidence: 99%